Chinese medicine Xiaoshui decoction inhibits malignant pleural effusion in mice and mediates tumor-associated macrophage polarization by activating autophagy. (1st March 2020) - Jin, Zhichao; Shen, Chunfeng; Zhang, Haidong; Qi, Runzhi; Guo, Qiujun; Liu, Rui; Hua, Baojin; Shi, Zhan
Abstract: Ethnopharmacological relevance: Xiaoshui decoction (XSD) is a traditional Chinese medicine compound prescription that has been shown to reinforce the spleen and remove the fluid retention, while being widely used in the treatment of malignant pleural effusion (MPE). We previously reported that XSD alleviates symptoms and improves the quality of life in patients with MPE; however, the mechanism employed by XSD on MPE has not yet been elucidated. Aim of the study: To investigate the role and mechanism of XSD in inhibiting the development of MPE, and in regulating macrophage polarization in vitro and in vivo . Materials and methods: A murine MPE model was used to study the effect of XSD on MPE. Mice with MPE were randomly allocated to a control group and XSD-low-dose (1.144 g/mL), XSD-middle-dose (2.288 g/mL), XSD-high-dose (4.576 g/mL), or cisplatin groups. RAW264.7 cells were induced to form tumor-associated macrophages (TAMs) as well as M1 and M2 macrophages using different conditioned media in vitro . Results: XSD effectively inhibited MPE formation, reduced pleural permeability and angiogenesis, and prolonged mice survival. Particularly, XSD treatment induced the polarization of TAMs to the M1 phenotype in MPE. Moreover, in-vitro XSD remarkably promoted the expansion of M1 macrophages and reduced M2 macrophages by enhancing autophagy. Conclusions: XSD inhibits MPE development and regulates macrophage polarization by activating autophagy, indicating that XSD may serve as a novel option for integrative MPE therapies. Graphical abstract: Image 1